Widespread shortfalls in protected area resourcing undermine efforts to conserve biodiversity - Coad, Lauren; Watson, James EM; Geldmann, Jonas; Burgess, Neil D; Leverington, Fiona; Hockings, Marc; Knights, Kathryn; Di Marco, Moreno (Frontiers in ecology and the environment, 2019)
Protected areas (PAs) are a key tool in efforts to safeguard biodiversity against increasing anthropogenic threats. As signatories to the 2011–2020 Strategic Plan for Biodiversity, 196 nations pledged support for expansion in the extent of the global PA estate and the quality of PA management. While this has resulted in substantial increases in PA designations, many sites lack the resources needed to guarantee effective biodiversity conservation. Using management reports from 2167 PAs (with an area representing 23% of the global terrestrial PA estate), we demonstrate that less than a quarter of these PAs report having adequate resources in terms of staffing and budget. Using data on the geographic ranges of the 11,919 terrestrial vertebrate species overlapping our sample of PAs, we estimate that only 4–9% of terrestrial amphibians, birds, and mammals are sufficiently represented within the existing global PA estate, when only adequately resourced PAs are considered. While continued expansion of the world's PAs is necessary, a shift in emphasis from quantity to quality is critical to effectively respond to the current biodiversity crisis.